Legalisasi Deklarasi HAM ASEAN - Imelda Masni Juniaty Sianipar (Universitas Muhammadiyah Yogyakarta, 2014)
On November 18, 2012, ASEAN countries signed ASEAN Human Rights Declaration. Since structured as a draft, this declaration has drawn controversy. The supporters argued that the declaration is a starting point for ASEAN countries to respect human rights. The Opponents considered that the declaration actually provide opportunities for ASEAN countries to commit human rights violations. Although both arguments are right, there is one thing that need to be underlined that the ten ASEAN countries have already signed the ASEAN Human Rights Declaration. This paper will examine the legalization of the ASEAN Human Rights Declaration. By examining its three dimensions -obligation, precision and delegation- ASEAN Human Rights Declaration is categorized as a soft legalization. The obligation of ASEAN Human Rights Declaration is low because it has no binding force. All ASEAN countries do not have obligation to implement the articles of the declaration. The precision of the declaration is also low because the words used in the declaration are ambiguous. It provides opportunities for the members of ASEAN countries to interpret them in different ways. Finally, the delegation of the declaration is also low because there is no third party that has authority to monitor the states’ compliance to the declaration and resolve conflicts that arise in case of human rights violations.